Custom-made micro applicators for high-dose-rate brachytherapy treatment of chronic psoriasis - Buzurovic, Ivan M.; O’Farrell, Desmond A.; Bhagwat, Mandar S.; Hansen, Jorgen L.; Harris, Thomas C.; Friesen, Scott; Cormack, Robert A.; Devlin, Phillip M. (Journal of Contemporary Brachytherapy, 2017)
Purpose: In this study, we present the treatment of the psoriatic nail beds of patients refractory to standard therapies using high-dose-rate (HDR) brachytherapy. The custom-made micro applicators (CMMA) were designed and constructed for radiation dose delivery to small curvy targets with complicated topology. The role of the HDR brachytherapy treatment was to stimulate the T cells for an increased immune response. Material and methods: The patient diagnosed with psoriatic nail beds refractory to standard therapies received monthly subunguinal injections that caused significant pain and discomfort in both hands. The clinical target was defined as the length from the fingertip to the distal interphalangeal joint. For the accurate and reproducible setup in the multi-fractional treatment delivery, the CMMAs were designed. Five needles were embedded into the dense plastic mesh and covered with 5 mm bolus material for each micro applicator. Five CMMAs were designed, resulting in the usage of 25 catheters in total. Results: The prescription dose was planned to the depth of the anterior surface of the distal phalanx, allowing for the sparing of the surrounding tissue. The total number of the active dwell positions was 145 with step size of 5 mm. The total treatment time was 115 seconds with a 7.36 Ci activity of the 192Ir source. The treatment resulted in good pain control. The patient did not require further injections to the nail bed. After this initial treatment, additional two patients with similar symptoms received HDR brachytherapy. The treatment outcome was favorable in all cases. Conclusions : The first HDR brachytherapy treatment of psoriasis of the nail bed is presented. The initial experience revealed that brachytherapy treatment was well-tolerated and resulted in adequate control of the disease. A larger cohort of patients will be required for additional conclusions related to the long-term clinical benefits.